(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The Indian stock market is one of the earliest in Asiabeing in operation since 1875, but remained largely outside the globalintegration process until the late 1980s. A number of developing countries inconcert with the International Finance Corporation and the World Bank tooksteps in the 1980s to establish and revitalize their stock markets as aneffective way of mobilizing and allocation of finance. In line with the globaltrend, reform of the Indian stock market began with the establishment ofSecurities and Exchange Board of India in 1988. This paper empiricallyinvestigates the long-run equilibrium relationship and short-run dynamiclinkage between the Indian stock market and the stock markets in majordeveloped countries (United States, United Kingdom and Japan) after 1990 byexamining the Granger causality relationship and the pairwise, multiple andfractional cointegration between the Indian stock market and the stock marketsfrom these three developed markets. We conclude that Indian stock market isintegrated with mature markets and sensitive to the dynamics in these marketsin a long run. In a short run, both US and Japan Granger causes the Indianstock market but not vice versa. In addition, we find that the Indian stockindex and the mature stock indices form fractionally cointegrated relationshipin the long run with a common fractional, no stationary component and find thatthe Johansen method is the best reveal their cointegration relationship. The Indian stock market is considered to be one of theearliest in Asia, which is in operation since 1875. However, it remainedlargely outside the global integration process until 1991. A number ofdeveloping countries in association with the International Finance Corporationand the World Bank took steps to establish and revitalize their stock marketsas an effective way of mobilizing and allocation of funds. In line with theglobal trend, reform of the Indian stock market also started with theestablishment of Securities and Exchange Board of India (SEBI), although itbecame more effective after the stock market scam in 1991. With theestablishment of SEBI and technological advancement Indian stock market has nowreached the global standard. The major indicators of stock market developmentshow that significant development has taken in the Indian stock market duringthe post-reform period. This paper seeks to examine in this context whetherreform in the Indian stock market has led to integration with the developedstock markets in the world. The study finds that contrary to general belief,Indian stock market is not co-integrated with the developed market as yet. Ofcourse, some short-term impact does exist, although it is found to beunidirectional for obvious reasons. That is to say, the developed stockmarkets, viz., USA, UK and Hong Kong stock markets Granger cause the Indiastock market but not vice versa. However, the study does not find any causalitybetween the Japanese stock market and Indian stock market. It is derived fromthe study that although some positive steps have been taken up, which areresponsible for the substantial improvement of the Indian stock market, theseare perhaps not sufficient enough to become a matured one and hence notintegrated with the developed stock markets so far.